Synthesis and hydrolytic properties of polyphosphazene/(diamine)platinum/saccharide conjugates - Song, SC; Sohn, YS (ELSEVIER SCIENCE BV, 1998)
An antitumor (diamine)platinum moiety was introduced to poly(organophosphazene) by using dicarboxylate spacers, glutamate or aspartate. A liver targeting beta-galactosyl group was also bound to 5-carboxyl-1-pentoxy residue of poly(organophosphazene) by carboxy activation with mixed anhydride method. After characterization of these polymeric conjugates by means of multinuclear (H-1, P-31) NMR and IR spectroscopies, elemental analysis and gel-permeation chromatography (GPC), their in vitro hydrolytic behavior were measured by monitoring with GPC in sodium acetate buffer solutions. Hydrolytic properties of the conjugates were dependent on pH and temperature. Over 70% of the platinum moiety was released from the conjugates after incubation for 4 days both in acidic and basic buffer solutions whereas the conjugates were stable in the neutral pH solution. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: CISPLATIN; POLYMERS; CANCER; DRUGS